Economic management innovation: Sustainable economic strategy to face trade tariffs and global economic challenges - Rahmiyati, Nekky; Ratnawati, Tri (The Economics and Finance Letters, 2025)
The lack of innovative development in economic management as a sustainable strategy has a negative impact on the wider community. In facing increasingly complex global challenges, such as uncertainty in trade tariffs and climate change, society and entrepreneurs must collaborate to overcome them. It is urgent to conduct research to study these issues because of the negative impact of fraudulent practices that harm consumers, and there is a need for policy reform to improve public protection. Therefore, the purpose of this study is to analyze innovative strategies in economic management to increase company competitiveness and contribute to achieving national and international sustainable development goals. The research approach used was a combination of quantitative surveys, interviews, and qualitative observations. The sample consisted of 357 participants selected through purposive sampling from small and large companies in Surabaya. Data collection techniques included instruments, in-depth interviews, and direct observations. Analysis was performed using descriptive statistics with the help of SPSS Version 29.0. The results showed that public-private sector collaboration in implementing sustainable practices can increase economic efficiency, reduce unemployment rates, and lower carbon emissions. The conclusion is that innovation in economic management, continuously developed by companies in Surabaya, can achieve significant and sustainable economic growth. Practical implications for policymakers include formulating policies that support sustainable investment in Surabaya, thereby supporting the local, national, and global economy.